2022
DOI: 10.3390/fishes7050292
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Wild Schizothorax kozlovi in the Upper Yangtze River Based on mtDNA and Stable Isotopes, and Their Relationship with Ambient Temperature

Abstract: Schizothorax kozlovi, as an endemic and vulnerable fish of the upper Yangtze River in China, faces many threats. In order to expose the population structure of wild S. kozlovi, the carbon and oxygen isotopic ratios in the otoliths, and the gene sequences of two common mitochondrial markers (Cytb and COI) were investigated in four sampling locations, and then their relationship with ambient temperature was further investigated. In general, it exhibits limited geographic population structuring of S. kozlovi in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Therefore, research on and attention to the biology of S. kozlovi are urgently needed for sustainable resource conservation. Previously, researchers have conducted studies on growth, reproduction, diet, population, and diversity [ 15 , 17 , 18 , 19 , 20 , 21 ]. But there has been little focus on the characterization of the mitochondrial genome and phylogenetic analysis for S. kozlovi .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, research on and attention to the biology of S. kozlovi are urgently needed for sustainable resource conservation. Previously, researchers have conducted studies on growth, reproduction, diet, population, and diversity [ 15 , 17 , 18 , 19 , 20 , 21 ]. But there has been little focus on the characterization of the mitochondrial genome and phylogenetic analysis for S. kozlovi .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Heckel [30] recommend that the Schizothorax can be divided into three groups based on the shape of the head and the morphology of the mouth; Chen et al [31] suggested that the Schizothorax should be classified into two subgenera on the basis of the presence or absence of keratin at the anterior edge of the jaw. Moreover, researchers have previously used single mitochondrial gene such as Cyt b or COI to determine phylogenetic relationships for species among Schizothorax, which may lead to one-sided and biased conclusions [21,22,32]. Within this context, it is necessary to unite multiple makers from genomes to investigate the taxonomic and phylogenetic relationships for Schizothorax.…”
Section: Introductionmentioning
confidence: 99%